The use of IT‐based information services. Issue 2 (2014) - S.M. Zabed Ahmed
<x xml:space="preserve"> Abstract </x> Purpose – The aim of this paper is to investigate the current status of public universities in Bangladesh in terms of library resources and services, IT infrastructure and training requirements for the establishment of a centralized, networked electronic library for the universities in the country. Design/methodology/approach – A survey was conducted in March‐April 2012 to ascertain the level of library automation practices, access to online resources and IT facilities utilized by the public universities in Bangladesh. The survey questionnaire was distributed through post and emails directed to the university librarians. The librarians were also asked to identify the type of IT‐related training they had and the type of training they require. Findings – The survey results indicate that there are insufficiencies in library resources, automation practices, access to online resources and IT facilities in the universities. Although the use of computer and network technologies in older universities is reasonably high; newer universities are lagging far behind in the latest technology applications. The results also suggest significant training needs by the librarians across all areas of electronic information processing. Originality/value – This is the first time an attempt has been made to assess the readiness of the public universities in Bangladesh for implementing IT‐based information services. The paper also proposed a framework for implementing an integrated electronic library for the universities in the country to offer them better access to a wide range of online resources and services.